2023
DOI: 10.1007/s11524-023-00796-x
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Neighborhood Dynamics in Gun Violence Exposure, Community Health, and Concentrated Disadvantage in One Hundred US Cities

Daniel C. Semenza,
Richard Stansfield,
Ian A. Silver
et al.

Abstract: Gun violence imparts a tremendous human and financial toll on local communities. Researchers have documented extensive mental and physical health consequences of generalized violence exposure but few studies have analyzed the particular impacts of gun violence on community well-being using nationally comprehensive data. We leverage a unique database of almost 16,000 neighborhoods in 100 US cities (2014–2019) to examine how year-over-year rates of gun violence correspond to overall neighborhood well-being and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 34 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Research has demonstrated that GVE is associated with exacerbated disparities in socioeconomic opportunity and collective well-being . Our results suggest that primary prevention of firearm violence may be a critical avenue for reducing suicidal ideation and behavior among Black US adults.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Research has demonstrated that GVE is associated with exacerbated disparities in socioeconomic opportunity and collective well-being . Our results suggest that primary prevention of firearm violence may be a critical avenue for reducing suicidal ideation and behavior among Black US adults.…”
Section: Discussionmentioning
confidence: 64%
“…Research has demonstrated that GVE is associated with exacerbated disparities in socioeconomic opportunity and collective well-being. 34 Our results suggest that primary prevention of firearm violence may be a critical avenue for reducing suicidal ideation and behavior among Black US adults. Yet, it is also necessary to make culturally congruent resources available for those who have directly or vicariously been exposed to gun violence alongside opportunities for broader collective healing given the current absence of comprehensive prevention.…”
Section: Discussionmentioning
confidence: 73%